Using groupware software for office automation system at Faculty of Computer Science and Information technology (FSKTM), UPM. - Abdullah, Rusli (2001)
Groupware software like Lotus Notes / Domino, Microsoft Exchange, Groupwise and others are products of that is very suitable for developing applications of people to work together as a teamwork such as in office environment and others in order to increase productivity and quality in term of services and so on. This paper we will present the used of Lotus Notes or Domino software for developing and implementing the office automation system at Fakulti Sains Komputer dan Teknologi Maklumat (FSKTM) of Universiti Putra Malaysia (UPM).